Berth allocation and quay crane assignment/scheduling problem under uncertainty: a survey - Rodrigues, Filipe (2024)
Port terminals play a critical role in the context of world trade since they are the main nodes responsible for connecting sea and land transportation. There are several optimization problems arising in port terminals, and those involving berth allocation are among the most important ones. They constitute the first level of terminal planning operations. As a consequence, the corresponding decisions impact all the subsequent operations in the port terminals. Berth allocation decisions are often integrated with quay crane assignment and/or scheduling decisions. However, the quality of these decisions is greatly affected by unpredictable events that may occur frequently. Since 2006, different approaches have been proposed for solving general berth allocation problems under uncertainty. This paper provides an exhaustive survey of the works published in the literature addressing berth allocation and berth allocation and quay cranes assignment/scheduling problems under uncertainty. The publications are classified into three main classes of approaches: proactive, reactive, and proactive/reactive. An overview of the main methodologies proposed, including stochastic programming, robust optimization, fuzzy programming, and deterministic approaches, is provided. The common sources of uncertainty are identified, and the representation of the uncertain parameters is highlighted. The papers are also classified according to the main objectives to be optimized and the solution methods proposed. We identify several research trends, limitations in the current literature and future research directions.